Kualitas Semen Kambing Sapera yang Dibekukan dalam Pengencer Tris Kuning Telur dengan Imbuhan Pentoxifylline (QUALITY OF SAPERA BUCK SEMEN FROZEN IN TRIS EGG YOLK EXTENDER ADDED WITH PENTOXIFYLLINE) - Hidayati, Bq Hayyul; Arifiantini, Raden Iis; Karja, Ni Wayan Kurniani; Kusumaningrum, Diana Andrianita (Jurnal Veteriner, 2018)
The aim of this study was to determine the effective dose of pentoxyfilline (PTX) to improve the quality of sapera buck frozen semen in Tris Egg Yolk (TEY) extender. Two sexually mature sapera bucks aged 1.5 years old was used as semen source. Semen collected with artificial vagina. Fresh semen were evaluated macro and microscopically. Only ejaculates showing > 70% sperm motility were selected. Semen were divided into four aliquots tubes containing TEY extender with 0 mM, 3.5 mM, 5 mM and 6.5 mM PTX each tube. After dilution, semen were packed into mini straw (0.25 ml) and equilibrated at 5 oC for 4 hours, then frozen above liquid nitrogen vapors for 10 minutes before plunged into liquid nitrogen (-196 oC). Results of this study showed that 6.5 mM PTX addition to the TEY extender improve post-thaw semen motility (P<0.05) but not viability and plasma membrane integrity. It concluded that 6.5 mM PTX addition to TEY extender improved post-thaw sperm motility of sapera buck.
Keywords: antioksidan, pembekuan, pentoxifylline, kambing Sapera